SEMINAR BAGI WANITA AGAR MEMILIKI KEROHANIAN YANG BERKUALITAS DI KOTA PADANG - Megawathy Cathrine Sibarani; Yanto Paulus Hermanto (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
A woman must understand the meaning of the helping words and prayer pillars. The facts show that there are still too many women in small towns and big cities who do not understand the function of a helper and prayer pillar in every household. The method used is to hold seminars about women so that many have quality spirituality. Because by having spiritual qualities, they will understand the function of being a helper and prayer pillar. The seminar implementation was delivered to various interdenominational churches; the participants were women pastors and the seminar lecture method. This is done with the hope that all participants can convey. This was done with the hope that all participants would be able to convey the material they got in the seminar to their respective congregations in their local church. Due to the covid 19 pandemic, many events are being held via zoom. This is also used to follow up on the teaching that has been delivered so that they remain in the community who want to learn.